Synthetic Biology Speeds Up Drug Target Discovery - Xie, Yixuan; Yang, Yanfang; He, Yu; Wang, Xixi; Zhang, Peng; Li, Haocheng; Liang, Shufang (Frontiers in Pharmacology, 2020)
As a rising emerging field, synthetic biology intends to realize precise regulations of cellular network by constructing artificial synthetic circuits, and it brings opportunities to treat diseases and discover novel drug targets. Depending on the combination mode of different logic gates, various synthetic circuits are created and multilevel regulations are carried out. In given synthetic circuits, drugs often act as inputs to drive circuits operation. It is becoming popular to construct drug-responsive gene circuits for many disease models, including metabolic disease, immunity disease, cancer and bacterial infection. Synthetic biology works well in association with the CRISPR system for drug target functional screening. Remarkably more and more well-designed circuits are developed to discover novel drug targets and precisely regulate drug therapy for diseases.